1979
DOI: 10.1007/bf02773735
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of pure pancreatic juice in patients with chronic alcoholism

Abstract: To elucidate early biochemical changes of pancreatic juice and their reversibility in chronic alcoholics, pure pancreatic juice was collected from 23 chronic alcoholics by endoscopic retrograde catheterization of the papilla. Samples were collected at 1 minute intervals for 20 minutes after intravenous injection of secretin (Eisai, 1 U/kg) and for 10 minutes after CCK-PZ injection (Boots, 1 U/kg). Volume, bicarbonate concentration, protein concentration and three hydrolases were determined. Following results w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1986
1986
1998
1998

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…In European or American alcoholics apparently free of pancreatic lesions, protein concentration and output are increased if the patient is studied in the days following alcohol excess [11. 12], but only concentration is signifi cantly higher than in normal controls if pancreatic juice is collected 1-2 weeks after cessation of alcohol consump tion [9][10][11] while later this difference vanishes [15], Hyperconcentration of protein in the early stage of the disease was expected in view of the biochemical changes of pancreatic juice observed in chronic alcoholic patients and in the experimental data [27], This is now confirmed by the present finding: in cases of early CP. we demonstrate an increase in the total concentration of protein in pancreatic juice, when compared ot local controls; the lipase concen tration, even though the secretory level of lipase was low in that population, was also higher than in controls.…”
Section: Modifications Observed In Cp Compared To Local Controlssupporting
confidence: 78%
See 3 more Smart Citations
“…In European or American alcoholics apparently free of pancreatic lesions, protein concentration and output are increased if the patient is studied in the days following alcohol excess [11. 12], but only concentration is signifi cantly higher than in normal controls if pancreatic juice is collected 1-2 weeks after cessation of alcohol consump tion [9][10][11] while later this difference vanishes [15], Hyperconcentration of protein in the early stage of the disease was expected in view of the biochemical changes of pancreatic juice observed in chronic alcoholic patients and in the experimental data [27], This is now confirmed by the present finding: in cases of early CP. we demonstrate an increase in the total concentration of protein in pancreatic juice, when compared ot local controls; the lipase concen tration, even though the secretory level of lipase was low in that population, was also higher than in controls.…”
Section: Modifications Observed In Cp Compared To Local Controlssupporting
confidence: 78%
“…This has also been shown in Japan [10]. In apparently normal alcoholic Europeans, one study found a significant decrease in bicarbonate concentration and output with volume being unchanged [9], In the late calcified stage, bicarbonate secretion was even lower than in the non-calcified stage and did not respond to secretin, but it increased slightly after cerulein which suggests that this cerulein-induced bicarbonate se cretion may be derived from the acini.…”
Section: Modifications Observed In Cp Compared To Local Controlsmentioning
confidence: 81%
See 2 more Smart Citations
“…[37][38][39]. The effect of pancreozymin on acinar cells is potentiated by raised intrapancreatic cholinergic tone [40], The latter phenomenon, as well as the diminished release of anti-pan creozymin factors caused by chronic alcohol consumption [41], may mediate the increased response to pancreozymin.…”
Section: Pancreozymin Pathwaymentioning
confidence: 99%